Can malignant thyroid nodules be distinguished from benign thyroid nodules in children and adolescents by clinical characteristics? A review of 89 pediatric patients with thyroid nodules - Buryk, Melissa A; Simons, Jeffrey P; Picarsic, Jennifer; Monaco, Sara E; Ozolek, John A; Joyce, Judith; Gurtunca, Nursen; Nikiforov, Yuri E; Feldman Witchel, Selma (Thyroid (New York, N.Y.), 2015)
Thyroid nodules are less common in children than adults, but the risk of malignancy in thyroid nodules is much higher in children. The ability to characterize pediatric thyroid nodules has improved with the use of ultrasound-guided fine-needle aspiration, the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) classification system, and expanded molecular testing. Nevertheless, stratification criteria to predict thyroid malignancy in children are poorly defined. Our objective was to determine if clinical presentation and molecular genetics could predict malignancy in pediatric thyroid nodules. Retrospective chart review of patients ≤18 years of age at the Children's Hospital of Pittsburgh of the University of Pittsburgh Medical Center with the diagnosis of a thyroid nodule from January 2007 to January 2012 was conducted. Eighty-nine subjects fulfilled the inclusion criteria: 1) thyroid nodule ≥0.8 cm and biopsy (n=76), or 2) thyroid nodule ≥0.8 cm, no biopsy, and ultrasound follow-up for at least 2 years (n=13). Twenty-four (27%) of 89 patients were diagnosed with thyroid cancer (50% papillary thyroid carcinoma [PTC], 50% follicular variant of papillary thyroid carcinoma [FVPTC]). Features associated with malignancy included larger nodule size, palpable nodule, or palpable lymphadenopathy. There were no differences in presenting features between patients with PTC and those with FVPTC. Thyroid malignancy was diagnosed in all nine patients with a molecular abnormality (BRAF, RAS, RET/PTC, PAX8/PPARγ). Clinical features, FNA cytology, and molecular genetics are valuable tools to discriminate benign from malignant nodules in pediatric patients. This information is important to direct subsequent clinical management.